Coexistence of Trust and Opportunism in Cooperative Projects between Startups - Cordova Bicudo da Costa, Caroline; Reyes Junior, Edgar; de Oliveira Dias, Fagner (Organizações & Sociedade, 2022)
The present study starts from the paradox of the coexistence of opportunism and trust in inter- organizational relationships to analyze how opportunism and trust develop in cooperative projects between startups. To this end, six projects were analyzed through ten semi-structured interviews in the context of a multiple case study. The data were analyzed using the content analysis technique. As the main results, the coexistence of trust and opportunism was observed, and it did not threaten the continuity of cooperative projects. An interactional dynamic of opportunistic bases emerged when it was not possible to identify the integrity-based dimension of trust. Also, opportunism was not identified in projects where the integrity-based dimension existed. The study contributes to the literature on the coexistence of trust in the context of cooperation. There are no records of empirical research on the phenomenon in cooperative projects. The results also offer practical implications about the relevance of competencies that allow the management of relationships with different levels of trust and opportunism.